Tissue Nonspecific Alkaline Phosphatase (TNAP) Regulates Cranial Base Growth and Synchondrosis Maturation - Nam, Hwa K.; Sharma, Monika; Liu, Jin; Hatch, Nan E. (Frontiers in Physiology, 2017)
Hypophosphatasia is a rare heritable disorder caused by inactivating mutations in the gene (Alpl) that encodes tissue nonspecific alkaline phosphatase (TNAP). Hypophosphatasia with onset in infants and children can manifest as rickets. How TNAP deficiency leads to bone hypomineralization is well explained by TNAP’s primary function of pyrophosphate hydrolysis when expressed in differentiated bone forming cells. How TNAP deficiency leads to abnormalities within endochondral growth plates is not yet known. Previous studies in hypophosphatemic mice showed that phosphate promotes chondrocyte maturation and apoptosis via MAPK signaling. Alpl-/- mice are not hypophosphatemic but TNAP activity does increase local levels of inorganic phosphate. Therefore, we hypothesize that TNAP influences endochondral bone development via MAPK. In support of this premise, here we demonstrate cranial base bone growth deficiency in Alpl-/- mice, utilize primary rib chondrocytes to show that TNAP influences chondrocyte maturation, apoptosis and MAPK signaling in a cell autonomous manner; and demonstrate that similar chondrocyte signaling and apoptosis abnormalities are present in the cranial base synchondroses of Alpl-/- mice. Micro CT studies revealed diminished anterior cranial base bone and total cranial base lengths in Alpl-/- mice, that were prevented upon injection with mineral-targeted recombinant TNAP (strensiq). Histomorphometry of the inter-sphenoidal synchondrosis (cranial base growth plate) demonstrated significant expansion of the hypertrophic chondrocyte zone in Alpl-/- mice that was minimized upon treatment with recombinant TNAP. Alpl-/- primary rib chondrocytes exhibited diminished chondrocyte proliferation, aberrant mRNA expression, diminished hypertrophic chondrocyte apoptosis and diminished MAPK signaling. Diminished apoptosis and VEGF expression were also seen in 15 day-old cranial base synchondroses of Alpl-/- mice. MAPK signaling was significantly diminished in 5 day-old cranial base synchondroses of Alpl-/- mice. Together, our data suggests that TNAP is essential for the later stages of endochondral bone development including hypertrophic chondrocyte apoptosis and VEGF mediated recruitment of blood vessels for replacement of cartilage with bone. These changes may be mediated by diminished MAPK signaling in TNAP deficient chondrocytes due to diminished local inorganic phosphate production.